ANALISIS ARUS KAS PADA UD. MARGA DINATA CELL DI SAMARINDA - Mardiana, Rinus Baene H. Eddy Soegiarto K (EKONOMIA, 2015)
This study aims to determine the operational activities, funding, investment cash flow generated from operating activities and sales at UD. Marga Dinata Cell Samarinda.               Accurate financial information in decision-making is the cash flow statement. Cash flows in a company, it is useful to users of the financial statements as a basis for assessing the ability of the company to achieve cash and cash equivalents in the assessment of the company needs to put on cash flow.               Cash is the most useful concept funds, because the decision of the investors, creditors and other parties focused on the assessment of future cash flows. The company will utilize idle cash by investing in a very short ranges investment likiud.               Financial report is basically the result of the accounting process that can be used as a tool for communication between financial data or activities of a company with the parties concerned with the data or activities of the company.               Users of financial statements includes current investors and potential investors, employees, lenders, suppliers and other business creditors, customers, governments and institutions and will use the information society in which the financial statements are different.               The foregoing description can be expressed as the following hypothesis: "the operational activities, investing, and financing affect the increase in cash flow in 1013 than in 2013.               The analytical tool used by researchers is to compare the financial statements prepared by UD. Marga Dinata Cell samarinda in 2011.2012, 2013 and arranged SAK applicable, comparing the cash flow statement is based on data obtained from UD. Marga Dinata Cell Samarinda.               Range of research directed at the analysis of cash flow and cash flow by operating activities, investing, financing UD. Marga Dinata Cell Samarinda. Based on the calculation of net income from 2012 Rp. 129 498 835, - in 2013 Rp. 283 154 500, - thus an increase in net profit of Rp. 153 655 665, -. Looking at the amount of cash and cash equivalents at the end of 2012 Rp. 77,924,165, - as well as cash and cash equivalents at the end of 2013 Rp. 185 786 315, - an increase of Rp. 123 986 315, -.            Thus it can be concluded that the hypothesis proposed by the author is accepted as cash flow at UD. Marga Dinata Cell in Samarinda had passed.